Use of satellite remote sensing in Malaysian forestry and its potential - Jusoff, Kamaruzaman; Souza, G.D. (Informa UK Limited, 1997)
The use of satellite remote sensing in Malaysian forestry and its potential are discussed under three headings (1) Application of satellite remote sensing in Malaysian forestry; (2) Current efforts in remote sensing research application; (3) Potentials of remote sensing techniques in monitoring logging operations and forest change; and remote sensing as a tool in rehabilitation and reforestation. It is concluded that there is a high potential of satellite remote sensing application in Malaysia, especially with the Landsat and SPOT data supported with aerial photographs. This is due to its fast delivery of relevant, timely and accurate information needed for sustainable forestry and a sound management decision.